A Study on the Financial Analysis of the Indian Banking Sector: Evaluating the Impact of Financial Sector Reforms on Indian Banking Industry (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Indian financial services industry is dominated by thebanking sector that contributes significantly to the level of economicactivity, as empirically demonstrated by Jadhav and Ajit (1996). The bankingstructure in India is broadly classified into public sector banks, privatesector banks and foreign banks. The public sector banks continue to dominatethe banking industry, in terms of lending and borrowing, and it has widelyspread out branches. Deregulation of the Indian financial system in 1991followed by various financial sector reforms during the period 1990 through1998 led to a major restructuring of the Indian banking industry. The reformswere based on the recommendations of the Committee on Financial Systems (CFS)(Narasimham 1991) first, followed by those of Committee on Banking SectorReforms (BSR) (Narasimham 1998) in a phased manner. The reforms werecomprehensive and led to sharp changes in various parameters of banking system.Further, on the basis of the recommendations of the Steering Committee set upby RBI, ‘Ownership and Governance’ and the implementation of the ‘New CapitalAdequacy Framework’ were formulated and issued to banks on February 15, 2005.As a result, the restrictions on geographical expansion and ceiling on interestrates were removed. With increased competition, declining margins on currentbusiness operations, higher costs and greater risks, banking industry ingeneral, had to face a two pronged challenge. They had on the one hand, toenhance their productivity and on the other, increase their ability to servethe nation in new ways with greater efficiency and effectiveness. In such ascenario, banking industry had to sustain itself by increased reliance on costminimization and by ensuring greater efficiency. These reforms were broadlyaimed to improve the performance of banks despite of the unexpected globalrecession and internal disturbances. At this juncture banking sector isimmensely competitive and growing in the right trend.